2012
DOI: 10.1007/978-1-61779-818-4_2
|View full text |Cite
|
Sign up to set email alerts
|

History of Plant Tissue Culture

Abstract: Plant tissue culture, or the aseptic culture of cells, tissues, organs, and their components under defined physical and chemical conditions in vitro, is an important tool in both basic and applied studies as well as in commercial application. It owes its origin to the ideas of the German scientist, Haberlandt, at the beginning of the twentieth century. The early studies led to root cultures, embryo cultures, and the first true callus/tissue cultures. The period between the 1940s and the 1960s was marked by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 90 publications
0
49
0
7
Order By: Relevance
“…Plantlet regeneration in conifers occurs by somatic embryogenesis and organogenesis, with the former being the preferred route [30]. More recently Bonga et al [31] have shown that, despite major advances in clonal propagation of woody species, somatic embryogenesis or organogenesis is still difficult [32] for many conifers; however, there are gaps in our knowledge in some areas which allow for a degree of skepticism. The paucity of knowledge controlling somatic embryogenesis, the synchrony of somatic embryo development and low frequency true to type embryonic efficiency are responsible for its reduced commercial application in forest trees [2].…”
Section: Discussionmentioning
confidence: 99%
“…Plantlet regeneration in conifers occurs by somatic embryogenesis and organogenesis, with the former being the preferred route [30]. More recently Bonga et al [31] have shown that, despite major advances in clonal propagation of woody species, somatic embryogenesis or organogenesis is still difficult [32] for many conifers; however, there are gaps in our knowledge in some areas which allow for a degree of skepticism. The paucity of knowledge controlling somatic embryogenesis, the synchrony of somatic embryo development and low frequency true to type embryonic efficiency are responsible for its reduced commercial application in forest trees [2].…”
Section: Discussionmentioning
confidence: 99%
“…Our data also show that sequential activation of WIND1 and an embryonic regulator LEAFY COTYLEDON2 enhances generation of embryonic callus, suggesting that combining WIND1 with other transcription factors promote efficient and organ-specific regeneration. Our findings in the model applied science (Thorpe 2012) but the molecular mechanisms of how plant cells modify developmental plasticity in response to various environmental stimuli, especially wounding and hormonal treatment, is just beginning to be understood.…”
Section: Introductionmentioning
confidence: 94%
“…The major shortcoming of vegetative propagation is limited rate of seed multiplication leading to slow spread of new improved cultivars to growers. Micropropagation has emerged as one of the important global agro-technologies routinely used for rapid generation of high quality, uniform and disease-free planting material (Thorpe 2007). The potential of this technology has not been fully exploited as agri-business industry in developing countries due to high capital cost and difficulties encountered in selling high-priced tissue culture products.…”
Section: Introductionmentioning
confidence: 99%